A Decolonial Perspective on Online Media Discourses in the Context of Violence Against People With Disabilities in South Africa - Dalvit,Lorenzo (2022)
Abstract: As one of the most violent and unequal societies globally, South Africa is still profoundly shaped by a legacy of segregation and oppression. While race, gender and socio-economic status receive much attention, (dis)ability is an important yet often neglected dimension of inequality. In this article, I adopt a decolonial perspective in discussing online media articles about violence against people with disabilities. By focusing on stories related to issues that received extensive media coverage (e.g. mental health, police brutality and gender-based violence), I problematise the Eurocentric human-rights discourse informing public and scholarly discussions. I also explore the link between current understandings of (dis)ability and the legacy of a violent colonial and apartheid past. As a result of the intersectional nature of (dis)ability, many of the stories involve multiple layers of inequality and different forms of oppression. An explicit focus on extreme forms of institutional and physical violence, while restricting the scope of enquiry, brings the brutality of western modernity and its effects on the people affected into sharp focus. Legal recurse appears to lead to incomplete reparation at best while its failures perpetuate a cycle of marginalisation and oppression. Rather than problematising these structural failures as a result of western modernity and neoliberalism, the media inadvertently obfuscates such links by performing its normative, that is, by identifying and exposing individual culprits or by blaming contextual factors.